Perceived Situational Appropriateness as a Predictor of Consumers' Food and Beverage Choices - Giacalone, Davide; Jaeger, Sara R. (Frontiers in Psychology, 2019)
This research investigated whether perceived situational appropriateness (defined as the degree of fit between product and intended usage situations) is predictive of consumer choices for foods and beverages, on the theoretical premise that intended usage situation acts as a frame of reference in orienting choices. Extant research on the topic, though suggestive of a link, is very limited in scope and almost completely lacking with regards to choice behaviour (as opposed to other aspects such as food acceptability or intake). To address the hypotheses, data collected in a series of 15 experiments ($N= 2731$ consumers in total) -- covering a wide range of product categories and usage situations -- are presented. In all studies, participants evaluated a set of stimuli varying with respect to perceived appropriateness (low to high), and evaluated each stimulus either monadically using a choice likelihood scale or by performing a discrete choice task. Regression analyses from all studies consistently indicated that perceived appropriateness significantly predicted choice response. The results were robust with respect to variation in product category and experimental protocol and, overall, strongly support the notion that appropriateness can provide a simple yet powerful (in some case accounting for over 50% of variance) predictor of consumer choice. Effect sizes varied substantially: perceived appropriateness explained from a minimum of 3% to over 65% of variance in consumer choice, and this variation was linearly related to the degree of product heterogeneity in the product sets. This research also investigated possible moderators of the link between appropriateness and choice, by relating the results to consumers’ product familiarity and involvement. While both traits significantly (and positively) affected choice, they did not interact with appropriateness. Possible explanations for these results, as well as other possible candidate moderators to explore in future research, are highlighted.